2019
DOI: 10.3892/etm.2019.7227
|View full text |Cite
|
Sign up to set email alerts
|

Expression of galectin‑3 and apoptosis in placental villi from patients with missed abortion during early pregnancy

Abstract: The success of a pregnancy relies on moderate trophoblast apoptosis. If the ‘inhibition-induction’ balance of apoptosis is broken, a pathological pregnancy may occur. Galectin-3 has an important role in numerous biological processes, including tumor cell apoptosis. However, the association between galectin-3 and missed abortion (MA) has remained elusive. In the present study, the mRNA and protein expression levels of galectin-3 in placental villi, and the apoptotic index of placental cells from patients with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(42 reference statements)
0
12
0
2
Order By: Relevance
“…In support of this notion, it has been shown that maternal gal‐3 circulating levels are decreased after the onset of missed abortion 29 . In addition, dysregulation of gal‐3 in placental villi has also been described for patients with missed abortion and may explain the observed dysregulation of peripheral gal‐3 levels 30 …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In support of this notion, it has been shown that maternal gal‐3 circulating levels are decreased after the onset of missed abortion 29 . In addition, dysregulation of gal‐3 in placental villi has also been described for patients with missed abortion and may explain the observed dysregulation of peripheral gal‐3 levels 30 …”
Section: Discussionmentioning
confidence: 87%
“…29 In addition, dysregulation of gal-3 in placental villi has also been described for patients with missed abortion and may explain the observed dysregulation of peripheral gal-3 levels. 30 An additional aim of this study was to determine the kinetics of the circulating maternal gal-3 throughout gestation, evaluating both uneventful pregnancies and development of GDM. We report here that serum gal-3 levels were reduced in patients that developed GDM.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that galectin-3 stimulates angiogenesis through the VEGF receptor dependent pathway and may also inhibit apoptosis in different types of cells. These galectin-3 functions may be pivotal in the pathophysiology of PE [ 51 , 52 ].…”
Section: Uterine Spiral Artery Remodelingmentioning
confidence: 99%
“…Missed abortion (MA) is a specific type of spontaneous abortion, and refers to the embryo or fetus dying in the uterine cavity but failing to spontaneously excrete in time prior to 20 weeks of gestation 1 The incidence of MA accounted for about 15% of all clinically recognized pregnancies, 2 which showed a rising trend in recent years. 3 In the process of MA, placental tissue closely adheres to the uterine wall, causing difficulty in curettage, 4 which makes women facing the high risk of severe bleeding, endometrial injury, infection and other complications. Due to the lack of obvious and specific symptoms, women experiencing a MA may have no self-awareness.…”
Section: Introductionmentioning
confidence: 99%